Brain permeability of bilobalide as probed by microdialysis before and after middle cerebral artery occlusion in mice - Lang, Dorothee; Ude, Christian; Wurglics, Mario; Schubert-Zsilavecz, Manfred; Klein, Jochen (Journal of Pharmacy & Pharmaceutical Sciences, 2010)
ABSTRACT. Purpose. Bilobalide is an active constituent of Ginkgo biloba and has shown neuroprotective effects in mice with cerebral ischemia. In the present study, we investigated brain permeability of bilobalide (i) in healthy mice and (ii) in mice before or after stroke. Methods. We have used in vivo microdialysis and LC-MS to estimate extracellular levels of bilobalide. 10 mg/kg of bilobalide was given by i.p. injection to control mice, and 60 minutes before and after middle cerebral artery occlusion (MCAO). Results. Bilobalide was already detectable in brain striatal microdialysates 10 min after i.p. administration and reached maximum levels (19 ng/mL, corresponding to 0.92 µM) after 40 min. Maximum plasma bilobalide levels were 5.9 µM. After an ischemic insult, the drug could be dialysed with similar efficiency as in control mice indicating slow elimination from the ischemic brain. When the drug was given after MCAO, availability in the brain was low, but measurable, at approx. 10% of control values. Conclusions. Our data demonstrate that bilobalide easily crosses the blood brain barrier and reaches extracellular concentrations in the brain that allow efficient interaction with target molecules such as neurotransmitter receptors. Availability of the drug in ischemic tissue is high when given before ischemia, but severely limited after MCAO.